Interpretacja jako inspiracja? Dekoracja drzwi do kruchty katedry poznańskiej - Ryba, Grażyna (Artium Quaestiones, 2018)
In the southern porch of the Poznań cathedral there is a swinging door etched in bronze and brass, made in 1972. Together with a bronze bas-relief placed above, it was the most important element of the decoration of the passage from the residence of Poznań archbishops to the cathedral. Both artworks were made by Ireneusz Daczko and Bogdan Fijałkowski – graduates of the Poznań Academy of Fine Arts. Their project was inspired by Rev. Stefan Tomaszkiewicz, who supervised construction work in the cathedral, and Rev. Bolesław Dzierwa, involved in the restoration of the cathedral in Gniezno. Both priests developed an original iconographic program of the porch decoration, based upon angelistic, christological, and mariological symbolism and texts in Polish, Latin, and Greek. The figures of archangels Gabriel and Michael in the door panels have a border with inscriptions, monograms, angels, and zoomorphic motifs, and objects intertwined with climbing plants. The decoration of the door and the bas relief showing the Assumption of Mary includes many references to the liturgy of the breviary, and points to the clergy as the recipients of the ideas represented in the porch iconography. The main argument of the paper is that the iconography of the Poznań door derives from the texts by Lech Kalinowski and, above all, Zdzisław Kępiński, who in his article, “The Symbolism of the Gniezno Door,” was the first to emphasize the significance of the border and the connection of its decoration with the correspondent figural panels of the bronze Gniezno door.